A human rights-consistent approach to multidimensional welfare measurement applied to sub-Saharan Africa - Arndt, Channing; Mahrt, Kristi; Hussain, M. Azhar; Tarp, Finn (Elsevier, 2018)
We discuss and compare the properties of the multidimensional poverty index and first-order dominance approach and apply both measures to 26 African countries using data near 2002 and 2012. Results across the two measures are broadly similar but not the same. For example, while the multidimensional poverty index suggests that all countries are advancing, FOD indicates that 14 countries experience broad-based progress, two countries show more moderate likelihoods of progress, and the remaining 10 countries neither improve nor deteriorate in terms of attainment of rights for the dimensions considered. We conclude that the multidimensional poverty index and first-order dominance approaches are useful complements that should be employed in tandem.